THE IMPACT OF KREDIT USAHA RAKYAT (KUR) ON MICRO, SMALL AND MEDIUM ENTERPRISES: EXAMINING FINANCIAL DISCIPLINE AND DEBT BURDEN WITHOUT BUSINESS EXPANSION - Mardanugraha, Eugenia Mardanugraha; Sugiharso, Sugiharso Safuan; Agriva, Maria Agriva; Benedict, Benedict Yappy (International Journal of Current Practice in Management and Leadership (IJCPML), 2023)
This study aimed to examine the impact of the Kredit Usaha Rakyat (KUR) government credit program on micro, small, and medium enterprises (MSMEs) in the Greater Jakarta Area. A sample of 701 MSME owners was surveyed to analyze the impact of KUR on financial discipline, debt management, investment, and consumption behavior of households. The study found that KUR increased the households’ financial discipline in terms of separating personal and business bank accounts, but it did not improve their ability to expand their businesses or change their consumption behavior from consumptive to productive. Additionally, KUR, when combined with credit from other sources, increased the outstanding debt of households owning MSMEs and indirectly increased household consumption. The study suggests that the psychological and sociological aspects of business owners’ consistency in running a business and expanding market reach are also important. The findings of this study hold significant implications for policymakers in developing MSMEs where focus should not only be on financing. Developing MSMEs in Indonesia requires a novel scheme that focuses not only on financing but also considers the psychological and social aspects of the MSME owners in developing the started enterprise.